Exploring Voice Agent Gender in a Running Coach Application - O'Neill, Casey (University of Waterloo, 2025)
In daily life, people commonly use voice agents such as Siri and Alexa to perform everyday tasks. With rapid technological advancements, voice agents are becoming more humanlike and there is a growing interest to use them in high-stakes tasks such as mental health advice and therapy. However, it is important to understand the potential harms posed by these voice agents of the future. This work focuses on gender-based social justice problems introduced by the widespread use of humanlike gendered voice agents, many of which disproportionately affect women due to the high prevalence of commercial voice agents that are female or ``female by default''. To contribute to an understanding of how to design gendered voice agents that reduce these potential harms, we explore reactions to a gendered voice agent running coach. We build a voice agent running coach system for smartphones that includes three voice options (male, female, gender ambiguous) which we validate through an in-person survey study (n = 30). We use our system in a field study (n = 18) in which participants run with the agent for three weeks and attend two in-person or online sessions with the researcher. We present a statistical analysis of survey data and key themes from a reflexive thematic analysis of interview data from the study. We conclude with a discussion of actions designers can take to create gendered voice agents more responsibly. We also offer recommendations for future research into gender and gender-based stereotyping in voice agents.
Keywords: human-computer interaction; voice agents; voice assistants; gender; gender stereotypes